Relasi Kekristenan dengan Agama-Agama Lain dalam Konteks Indonesia - Herman Sjahthi; Albert Sahala; Benediktus James Widya Darmaka (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2026)
Religious pluralism is an unavoidable reality in Indonesian society, where people from diverse religious, cultural, and ethnic backgrounds coexist. This study examines the relationship between Christianity and other religions, focusing on Christology and the doctrine of salvation within the context of Indonesian pluralism. The research aims to explore how Christians can maintain faithfulness to biblical teachings while fostering tolerance, respect, and harmonious interreligious relations. This study employs a qualitative literature review method by analyzing biblical texts, theological literature, scholarly articles, and perspectives from Christian theologians concerning religious diversity, the uniqueness of Jesus Christ, and Christian engagement in a pluralistic society. The findings indicate that Christianity upholds the exclusive claim that Jesus Christ is the Savior and the only way to salvation, while simultaneously teaching values of love, compassion, justice, and peace toward all people regardless of their religious affiliation. The study further reveals that constructive interfaith dialogue does not require compromising core Christian doctrines but encourages mutual understanding and cooperation for the common good. In the Indonesian context, the church is challenged to develop a contextual, dialogical, and transformative apologetic approach that reflects Christ’s love and promotes social harmony. Therefore, Christian witness can remain faithful to its theological foundations while contributing positively to peacebuilding, national unity, and the development of a just and inclusive society.